2004
DOI: 10.1080/02724980343000189
|View full text |Cite
|
Sign up to set email alerts
|

Inspecting Pictures for Information to Verify a Sentence: Eye Movements in General Encoding and in Focused Search

Abstract: When we see combinations of text and graphics, such as photographs and their captions in printed media, how do we compare the information in the two components? Two experiments used a sentence-picture verification task in which statements about photographs of natural scenes were read in order to make a true/false decision about the validity of the sentence, and in which eye movements were recorded. In Experiment 1 the sentence and the picture were presented concurrently, and objects and words could be inspecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
63
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 26 publications
8
63
3
Order By: Relevance
“…The duration of the first inspection of an object or word is often an indication of the difficulty of processing (see, for example, Rayner, 1998;Underwood et al, 2004), and so gaze duration may also be indicative of the difficulty of recognising the objects in the pictures shown here. Gaze is defined as the total of all fixations made on the object prior to a fixation upon another object.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The duration of the first inspection of an object or word is often an indication of the difficulty of processing (see, for example, Rayner, 1998;Underwood et al, 2004), and so gaze duration may also be indicative of the difficulty of recognising the objects in the pictures shown here. Gaze is defined as the total of all fixations made on the object prior to a fixation upon another object.…”
Section: Resultsmentioning
confidence: 99%
“…Fixation patterns made on pictures accompanied by text support the view that the gist can be determined during the first few fixations, and that an extended search is not necessary in order to build a representation of the main features of the picture. In a range of tasks viewers characteristically move their gaze from the graphical component after just two or three fixations, in order to read the accompanying text in a mixed display (Carroll, Young & Guertin, 1992;Rayner, Rotello, Stewart, Keir & Duffy, 2001;Underwood, Jebbett & Roberts, 2004). The early departure from scene to text suggests that sufficient information can be extracted during this time to develop a representation that can be used for reference when reading the sentence.…”
mentioning
confidence: 99%
“…Empirical studies showed no clear result pattern regarding the preferred order of information extraction. Whereas Hegarty and Just (1993) showed that participants looked first at the verbal information, other studies found initial processing of the pictorial information (Rayner, Rotello, Steward, Keir, & Duffy, 2001;Underwood, Jebbett, & Roberts, 2004;Stone & Glock, 1981) suggesting different (task-dependent) strategies.…”
Section: Processing Of Visual Informationmentioning
confidence: 99%
“…Many early experiments were concerned with eye movements and long-term picture memory (Loftus, 1972;Nelson & Loftus, 1980), whereas more recent work has investigated the memory representations that are formed online during scene viewing (e.g., Henderson & Hollingworth, 2003;Hollingworth & Henderson, 2002;Hollingworth, Schrock, & Henderson, 2001;Zelinsky, 2001) and the search of scenes prompted by the evaluation of accompanying text (Underwood, Jebbett, & Roberts, 2004). One key finding that has emerged from these studies is that memory for pictorial detail is highly contingent upon fixation behavior.…”
mentioning
confidence: 97%